1997
DOI: 10.1007/s004649900542
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic colposuspension using mesh reinforcement

Abstract: Laparoscopic Burch colposuspension using mesh reinforcement provides durable resolution of stress incontinence with low risk of conversion, short hospitalization, and few complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Modified laparoscopic techniques fixing strips of hernia mesh to the paraurethral tissue and Cooper's ligament using surgical staples or a tacking device were described to replace endoscopic suture suspension [8–10]. These new developments were proposed to reduce the technical complexity of laparoscopic colposuspension while still maintaining a high success rate [10–13].…”
Section: Introductionmentioning
confidence: 99%
“…Modified laparoscopic techniques fixing strips of hernia mesh to the paraurethral tissue and Cooper's ligament using surgical staples or a tacking device were described to replace endoscopic suture suspension [8–10]. These new developments were proposed to reduce the technical complexity of laparoscopic colposuspension while still maintaining a high success rate [10–13].…”
Section: Introductionmentioning
confidence: 99%
“…It was initially unclear whether 2 sutures were better than mesh and staples techniques. 12,13,19,26 Early results showed that the mesh seemed to be as effective as suture 18 ; however, recent data suggest laparoscopic suture is better than prolene mesh, 15 because of a significantly lower objective cure rate in the LSC mesh group at 36 months compared with the suture group (39% vs. 57%, P Ͻ 0.05).…”
Section: Discussionmentioning
confidence: 79%
“…[12][13][14][15][16][17][18] The surgical technique in the current study involved placing 2 sets of permanent supportive sutures bilaterally (Gore-tex THX-26; catalog no. 2N05; suture length 36 in) for both the intraperitoneal laparoscopic and open Burch approach.…”
mentioning
confidence: 99%
“…Mesh reinforcement is thought to add durability to laparoscopic colposuspension. The synthetic mesh is held in place with tackers, which avoids laparoscopic suturing within the confined pelvic space 3 . A study involving 5‐year follow up of laparoscopic colposuspension with synthetic mesh and staples, showed an initial success rate of 90% and 5‐year cure in 88% 4 …”
Section: Discussionmentioning
confidence: 99%
“…The synthetic mesh is held in place with tackers, which avoids laparoscopic suturing within the confined pelvic space. 3 A study involving 5-year follow up of laparoscopic colposuspension with synthetic mesh and staples, showed an initial success rate of 90% and 5-year cure in 88%. 4 We are not aware of any previously reported case of mesh erosion into the bladder following laparoscopic colposuspension.…”
Section: Discussionmentioning
confidence: 99%